Cerebral venous sinus thrombosis. (February 2015) - Hartel, Marcin; Kluczewska, Ewa; Gancarczyk-Urlik, Eliza; Pierzchała, Krystyna; Bień, Karolina; Zastawnik, Anna
Diagnostic imaging in cerebral venous sinus thrombosis poses difficulties due to the relatively rare incidence of this pathology and its usually inconclusive clinical and radiological symptoms. The preliminary examination is usually performed using computed tomography, whereas magnetic resonance imaging (MRI) provides better visualisation of the lesion. Computed tomography and magnetic resonance imaging angiography enable the characterisation of the blood flow in the pathologically affected vessels in more detail. Familiarity with the anatomic variations of the venous system and with the advantages and limitations of computed tomography/magnetic resonance imaging enables faster diagnosis of the pathology. This is significant for treatment, which, in many cases, can be efficient only if introduced at a sufficiently early stage.